Kedudukan Anak dari Perkawinan Berbeda Agama menurut Hukum Perkawinan Indonesia - Fitria Agustin (Universitas Serang Raya, 2018)
Article 2 paragraph (1) of Law Number 1 Year 1974 contains provisions that marriage shall be considered valid if done according to the law of their respective religion and belief. The above provision implies no marriage outside the law of each of his or her religion and belief. Intermarriages between people of different religions will obviously cause problems as a result of the law of their marriage, most of which include the rights and duties of each husband and wife, property in marriage, as well as the position of the child in a marriage relationship. Problems will arise when the child has been born starting from the pattern of upbringing until when the child is adult and ably performs legal acts such as marriage, inheritance, and so forth. This research is intended to get answers to the problems: (1) How the position of the Child from Marriage parents of different religions? 2) How does the child's relationship with her parents' parent if the child chooses a religion differently from both parents? The invention of the answer to this question is pursued by the Empirical Normative Legal Research Method. The law acts as a Norm (Legislation), with due regard to social reality. The results of the study are: (1) The marriage of religious differences according to the Marriage Law is considered invalid as well as the child born of the Marriage. (2) A child born of a different religious marriage only has a nasab with his mother.